STRESS AND ANXIETY IN ROMANIAN COVID-19 PATIENTS: THE ROLE OF ALCOHOL, SMOKING, AND THE PSYCHOLOGICAL IMPACT OF THE PANDEMIC - Ioana Silistraru; Radu Petru Soroceanu; Radu Gheorghe Grigore; Mihaela Moscalu; Anisia-Iuliana Alexa; Ioan-Adrian Ciureanu (Romanian Journal of Oral Rehabilitation)
This cross-sectional study explores the impact of behavioural factors on perceived stress and anxiety in COVID-19 positive and negative patients in Romania (N=1362). While focusing on identifying the main anxiety and stress predictors, data were gathered based on demographic criteria, alcohol consumption, tobacco use, and anxiety scores measured with Hamilton Anxiety Rating Scale (HAM-A) among two groups of inpatients: both with positive and negative COVID-19 tests. The relationship to the Perceived Stress Scale (PSS) scores was assessed through regression analysis. Study results suggest that in the COVID-19 positive group, alcohol consumption was associated with higher perceived stress, while smoking was associated with lower stress scores. In both groups anxiety levels predicted a high perceived stress, suggesting that high levels of anxiety were pervasive during the pandemic. However, demographic factors such as age, gender, income level were significant predictors of stress in COVID-19 negative group, whereas in the positive group the demographics showed no significant impact. Our study findings suggest that maladaptive behaviours should be addressed, and public health interventions should be considered globally to mitigate post-pandemic stress effectively.